A new robust adaptive mixing control for trajectory tracking with improved forward flight of a tilt-rotor UAV. (April 2021) - Cardoso, Daniel N.; Esteban, Sergio; Raffo, Guilherme V.
Abstract: A new robust adaptive mixing control (RAMC) is proposed in order to accomplish trajectory tracking of a tilt-rotor unmanned aerial vehicle (UAV) configuration. This kind of system is a hybrid aerial vehicle that combines advantages of rotary-wing aircraft, like hovering flight and vertical take-off and landing (VTOL), and those of fixed-wing aircraft, as improved forward flight. Although the VTOL and cruise flight regimes present different dynamic behaviors, in this work a unified, highly coupled, nonlinear model is developed to cope with the considered tilt-rotor UAV full flight envelope, that is, the axial flight, hovering, transition/cruise and turning flight. The modeling is performed via Euler–Lagrange formulation considering the tilt-rotor UAV as a multi-body system and taking into account aerodynamic effects and the dynamics of the tilting servomotors. Accordingly, in order to comply with the trajectory tracking requirements and improve the tilt-rotor UAV forward flight, this paper presents a novel robust adaptive mixing controller which is formulated to deal with linear parameter-varying (LPV) systems dependent on not known a priori large parameters but measured or estimated online, and also to provide robustness against unknown disturbances. Additionally, a rigorous closed-loop stability analysis is performed. The controller performance is validated with numerical experiments conducted using a high fidelity simulator developed on Gazebo and Robot Operating System (ROS) platforms. Highlights: A tilt-rotor UAV multi-body dynamic model formulated via the Euler–Lagrange approach. A new robust AMC for polytopic uncertain systems in the state-space. RAMC synthesis for full flight envelope trajectory tracking of a tilt-rotor UAV. Stability proof of the new RAMC for the full flight envelope trajectory tracking.